Measuring Urban Streetscapes for Livability: A Review of Approaches. Issue 1 (2nd January 2016) - Harvey, Chester; Aultman-Hall, Lisa
Abstract : Increasing interest in urban livability demands that geographers and planners more precisely define what constitutes a livable streetscape, a fundamental building block of urban places. Widespread examination of streetscape livability will require precise and efficient measurements of (1) physical characteristics at the spatial scale of individual streetscapes and (2) indicators of experiential quality based on revealed behavior or stated preference. This article reviews approaches to collecting both types of measurements, showing that innovative methods using geographic information systems (GIS), Internet-enabled surveys, and even social media could be useful complements to traditional qualitative methods for collecting streetscape measurements.